Medio-Lateral Postural Instability in Subjects with Tinnitus - Kapoula, Zoi; Yang, Qing; Le, Thanh-Thuan; Vernet, Marine; Berbey, Nolwenn; Orssaud, Christophe; Londero, Alain; Bonfils, Pierre (Frontiers in Neurology, 2011)
Background: Many patients show modulation of tinnitus by gaze, jaw or neck movements, reflecting abnormal sensorimotor integration and interaction between various inputs. Postural control is based on multi-sensory integration (visual, vestibular, somatosensory, and oculomotor) and indeed there is now evidence that posture can also be influenced by sound. Perhaps tinnitus influences posture similarly to external sound. This study examines the quality of postural performance in quiet stance in patients with modulated tinnitus. Methods: Twenty-three patients with highly modulated tinnitus were selected in the ENT service. Twelve reported exclusively or predominately left tinnitus, eight right and three bilateral. Eighteen control subjects were also tested. Subjects were asked to fixate a target at 40cm for 51s; posturography was performed with the platform (Technoconcept, 40Hz) for both the eyes open and eyes closed conditions. Results: For both conditions, tinnitus subjects showed abnormally high lateral body sway (SDx). This was corroborated by fast Fourrier Transformation (FFTx) and wavelet analysis. For patients with left tinnitus only, medio-lateral sway increased significantly when looking away from the center. Conclusions: Similarly to external sound stimulation, tinnitus could influence lateral sway by activating attention shift, and perhaps vestibular responses. Poor integration of sensorimotor signals is another possibility. Such abnormalities would be accentuated in left tinnitus because of the importance of the right cerebral cortex in processing both auditory-tinnitus and attention.